2018
DOI: 10.2147/ott.s176534
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 is downregulated in osteosarcoma and facilitates EMT as well as migration through regulation of slug

Abstract: BackgroundGATA3 functions as a tumor suppressor and has been observed in multiple types of cancer, but the effects and mechanisms of GATA3 in osteosarcoma (OS) are not yet known.MethodsThe GATA3 expression in OS cells and tissues were detected using quantitative reverse-transcription PCR and Western blotting assay. CCK-8 assay, colony formation assay, wound healing assay as well as transwell assay, were performed to determine the effects of GATA3 on cell proliferation, migration and invasion. ChIP and qChIP as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…EMT serves key roles in cancer metastasis ( 27 ). In corroboration with previous studies ( 17 , 28 ), the present study demonstrated that GATA3 suppressed EMT in HCC cells by increasing the expression of E-cadherin and decreasing the expression of N-cadherin and vimentin. In addition, qChIP and dual luciferase reporter assays demonstrated that GATA3 transcriptionally regulated slug, thereby inhibiting EMT in HCC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…EMT serves key roles in cancer metastasis ( 27 ). In corroboration with previous studies ( 17 , 28 ), the present study demonstrated that GATA3 suppressed EMT in HCC cells by increasing the expression of E-cadherin and decreasing the expression of N-cadherin and vimentin. In addition, qChIP and dual luciferase reporter assays demonstrated that GATA3 transcriptionally regulated slug, thereby inhibiting EMT in HCC.…”
Section: Discussionsupporting
confidence: 93%
“…4A and C ). Notably, a previous study demonstrated that GATA3 regulates the expression of slug in osteosarcoma ( 17 ). Thus, whether GATA3 regulated slug expression in HCC was determined.…”
Section: Resultsmentioning
confidence: 99%
“…A reciprocal feedback regulatory loop between GATA3 / G9A / MTA3 and ZEB2 / G9A / MTA1 has recently been identified; the absence of GATA3 in this axis contributes to breast cancer invasion and metastasis by upregulating the ZEB2 expression levels ( 65 ). GATA3 has also been reported to suppress osteosarcoma EMT progression by targeting the transcription factor Slug ( 66 ). The present study demonstrated for the first time that GATA3 was involved in the immunomodulation of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the Wnt/beta-catenin signaling inhibits angiogenesis and induces cell apoptosis in osteosarcoma cells by inducing autophagy [ 38 ]. Inhibition of EMT serves as a tumor suppressor in osteosarcoma by suppressing the progression and metastasis [ 39 ]. Furthermore, EMT inactivation inhibited proliferation, migration, invasion, and in osteosarcoma by targeting zinc finger E-box-binding protein 1 (ZEB1) through inactivation of c-Jun N-terminal kinase (JNK) and JAK1/signal transducer and activator of transcription 3 (STAT3) pathways [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the Wnt/β-catenin and EMT signaling pathways are associated with tumor cell proliferation, apoptosis, and cell cycle regulation [37][38][39]. Aberrant activation of Wnt signaling has been implicated in human osteosarcoma, and Wnt/β-catenin signaling plays the critical role in human osteosarcoma pathogenesis and growth [37].…”
Section: Discussionmentioning
confidence: 99%